Who can help me? Understanding the antecedent and consequence of medical information seeking behavior in the era of bigdata - Sun, Jiwei; Zhang, Shujie; Hou, Min; Sun, Qian; Cao, Fenglin; Zhang, Zhonghao; Tang, Guiyao; Wang, Xingyuan; Geng, Ling; Cui, Linlin; Chen, Zi-Jiang (Frontiers in Public Health, 2023)
Introduction The advent of bigdata era fundamentally transformed the nature of medical information seeking and the traditional binary medical relationship. Weaving stress coping theory and information processing theory, we developed an integrative perspective on information seeking behavior and explored the antecedent and consequence of such behavior. Methods Data were collected from 573 women suffering from infertility who was seeking assisted reproductive technology treatment in China. We used AMOS 22.0 and the PROCESS macro in SPSS 25.0 software to test our model. Results Our findings demonstrated that patients’ satisfaction with information received from the physicians negatively predicted their behavior involvement in information seeking, such behavior positively related to their perceived information overload, and the latter negatively related to patient-physician relationship quality. Further findings showed that medical information seeking behavior and perceived information overload would serially mediate the impacts of satisfaction with information received from physicians on patient-physician relationship quality. Discussion This study extends knowledge of information seeking behavior by proposing an integrative model and expands the application of stress coping theory and information processing theory. Additionally, it provides valuable implications for patients, physicians and public health information service providers.